2009
DOI: 10.1136/emj.2008.063388
|View full text |Cite
|
Sign up to set email alerts
|

DNW--"Did Not Wait" or "Demographic Needing Work": a study of the profile of patients who did not wait to be seen in an Irish emergency department

Abstract: Failure to provide the service in a timely manner gives rise to patients leaving without receiving the medical assessment they came to obtain. This is a serious clinical problem and puts both those requiring care and those providing it at risk of adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 18 publications
3
26
4
1
Order By: Relevance
“…Our results are also in accordance with previous publications, showing that LWBS patients have a wide range of complaints, with musculoskeletal and gastrointestinal complaints ranked first, and a low acuity level [12, 29, 31]. Unlike other studies, complaints related to wounds are infrequent in our study, possibly reflecting a low rate of stab wounds [31].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in accordance with previous publications, showing that LWBS patients have a wide range of complaints, with musculoskeletal and gastrointestinal complaints ranked first, and a low acuity level [12, 29, 31]. Unlike other studies, complaints related to wounds are infrequent in our study, possibly reflecting a low rate of stab wounds [31].…”
Section: Discussionsupporting
confidence: 92%
“…15,16 In a study by Goldman et al, 13 patients were statistically more likely to LWBS if they presented during the night shift; similar results have been found in studies of adult patients who LWBS. 4,7,24 Rates of LWBS showed seasonal variations. Patients were more likely to LWBS if they presented to the ED during the winter and spring.…”
Section: Discussionmentioning
confidence: 99%
“…Like other studies, we found that patients who LWBS present with conditions of lower urgency, are more likely to be younger patients, to be male, to have arrived without assisted transport, to have self-referred, to be of indigenous Australian background, to be from non-English-speaking backgrounds, and to have arrived in the evening. 2,[15][16][17] The relationship of LWBS with indigenous status is important. Based on data from the Australian Bureau of Statistics, Victoria has a low level of indigenous population compared to the overall data for Australia; 18 however, the issues contributing to higher risk of LWBS for this patient population will need further exploration to tailor effective interventional strategies.…”
Section: Discussionmentioning
confidence: 99%